Pembelajaran Matematika Berbasis Computation Thinking di Era Kurikulum Merdeka Belajar di Sekolah Islam Terpadu Asy-Syifa Kota Jambi - Renda Pandu Winata; M. Syahran Jailani (Jurnal Bintang Pendidikan Indonesia, 2025)
This study is based on the importance of Mathematics Learning based on Computational Thinking in Asy-Syifa Islamic Schools, Jambi City, because some students at Asy-Syifa Islamic Schools, Jambi City have difficulty understanding the concept of learning mathematics, lack of practice, and even motivation factors. Therefore, the purpose of this study is to determine the planning, implementation and evaluation of Mathematics Learning Based on Computational Thinking in the Era of Independent Learning Curriculum in class IV of Asy-Syifa Islamic School, Jambi City. To achieve these goals, the researcher used qualitative research with the method used Phenomenology. The data collection techniques used in this study were observation, interviews and documentation. The data source selected was snowball sampling using respondents from the principal, class IVA mathematics study teachers and class IV students. The data analysis techniques used in this study were data reduction, data presentation and data conclusions. The results of this study are 1) Planning of Mathematics Learning Based on Computational Thinking in the Era of Independent Learning Curriculum in grade IV of Asy-Syifa Islamic School, Jambi City includes Introduction to Computational Thinking, Determining learning objectives, Mathematics learning design based on Computational Thinking, Development of media or learning tools, Learning activities, Learning assessment and improvement. 2) Implementation of Mathematics Learning Based on Computational Thinking in the Era of Independent Learning Curriculum in grade IV of Asy-Syifa Islamic School, Jambi City includes Decomposition (Problem Deconstruction), Implementation of technology, Collaboration and Discussion and evaluation and reflection. 3) Evaluation of Mathematics Learning Based on Computational Thinking in the Era of Independent Learning Curriculum in grade IV of Asy-Syifa Islamic School, Jambi City includes Understanding the basic concept of Computational Thinking, Implementation in learning, Assessment of Computational Thinking skills, Learning outcomes and feedback from students and teachers.